Joint physical custody, turning to parents for emotional support, and subjective health: A study of adolescents in Stockholm, Sweden. Issue 5 (July 2014) - Låftman, Sara Brolin; Bergström, Malin; Modin, Bitte; Östberg, Viveca
Aims: Among children with separated parents, the arrangement of joint physical custody, i.e. children living equally much in both parents' homes, has increased substantially during the last decades in Sweden. To date, empirical research on the living conditions of this group is limited. This study analyses family type differences in turning to parents for emotional support and in subjective health among adolescents. The focus of the study is adolescents in joint physical custody, who are compared with those living with two original parents in the same household; those living (only) in a single-parent household; and those living (only) in a reconstituted family. Methods : The data come from the Stockholm School Survey of 2004, a total population survey of students in grade 9 (15–16 years) in Stockholm ( n =8, 840). Ordinary least squares (OLS) regressions were conducted. Results : Turning to both parents about problems is most commonly reported by adolescents in intact families, followed by those in joint physical custody. Adolescents in non-traditional family types report worse subjective health than adolescents in intact families, but the difference is smaller for those in joint physical custody than for those living with a single parent. The slightly poorer health of adolescents in joint physical custody than those in intact families is not explained by their lower use of parents as a source of emotional support. Conclusions : The study suggests that joint physical custody is associated with a higher inclination to use parents as a source of emotional support and better subjective health than other post-divorce family types.